A Miniaturized Bandwidth Reconfigurable Bandpass Chip Filter with Semi‐lumped Topology and GaAs pHEMT Technology. Issue 1 (1st January 2021) - Linqing, Li; Haoran, Zhu; Xingyu, Ning; Zunwen, Li; Xianliang, Wu
Abstract : A miniaturized reconfigurable bandpass chip filter with semi‐lumped topology and Gallium Arsenide pseudomorphic High electron mobility transistor (GaAs pHEMT) technology is proposed. Semi‐lumped topology is employed to instead the traditional lumped inductor with microstrip transmission line, which can reduced the size of the tunable filter significantly. Three‐order series and shunt resonated bandpass filter is implemented with shorted stubs and metal‐insulator‐metal capacitors. Two transmission zeros are introduced with the series resonator and the shunted GaAs FET. By tuning the gate bias circuit of the FET, the capacitance of the series resonator is changed and the bandwidth of the filter is adjusted correspondingly. An equivalent circuit model is developed to interpret the mechanism of the proposed filter circuit. A reconfigurable on chip filter sample operated at 10GHz is fabricated to validate the design. Two fractional bandwidth of 14.3% and 23.5% are tuned with bias voltage of the FET, while insertion loss of 2.4dB and 2.2dB are observed with the filter, respectively. The area of the chip filter is 0.86 × 0.96mm 2 and is equivalent to an electrical length of 0.08 × 0.09λg 2 at center frequency. Measurement results agree well with the simulation ones.